2020
DOI: 10.3390/pr8091196
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of Recycled Pork Fat-Based Biodiesel in Aviation Turbo Engines

Abstract: This paper presents an analysis of the possibility of using recycled pork fat-based biodiesel as fuel for aviation turbo-engines. The analysis consists of the assessment of four blends of Jet A kerosene with 10%, 30%, 50%, and 100% biodiesel and pure Jet A that was used as reference in the study. The first part of the paper presents the physical-chemical properties of the blends: density, viscosity, flash point, freezing point, and calorific power. Through Fourier transform infrared spectroscopy (FTIR) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The measure of oil's flow characteristics though the significance of viscosity test results has been considered from the standpoint of new oils, these tests also have an essential place in the evaluation of base oils, as well as used formulated oils. In the present work, the kinematic viscosity of fresh Jatropha and modified Jatropha oil samples were determined according to the ASTM Standard D445-04 [9] and ASTM standard D446-04 [10] using U-tube viscometers at a constant temperature Flash point of the fresh oil samples was determined according to the ASTM Standard D92-05a [11].…”
Section: Experimental Workmentioning
confidence: 99%
“…The measure of oil's flow characteristics though the significance of viscosity test results has been considered from the standpoint of new oils, these tests also have an essential place in the evaluation of base oils, as well as used formulated oils. In the present work, the kinematic viscosity of fresh Jatropha and modified Jatropha oil samples were determined according to the ASTM Standard D445-04 [9] and ASTM standard D446-04 [10] using U-tube viscometers at a constant temperature Flash point of the fresh oil samples was determined according to the ASTM Standard D92-05a [11].…”
Section: Experimental Workmentioning
confidence: 99%
“…NO x and smoke emissions decreased by 20% and 60% with a 10% blend of PF with diesel, whereas hydrocarbon (HC) emissions increased by 54%. Cican et al [12] studied PF-based biodiesel in aviation fuel at fractions of 10%, 30%, 50% and 100% with JetA kerosene. It was observed that the addition of PF biodiesel increases the freezing point of the blend and thus necessitates heating at higher altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the noise and vibration level with the biodiesel blend are within the limits of functionality. Although studies are available on different routes of production of PF biodiesel, only limited research is available on the effects of PF biodiesel in engine application [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted aiming to assess the use of alternative fuels in turbo engines, consisting of both in lab and in-flight assessment [ 20 , 21 , 22 ]. Other studies that are evaluating the combustion and gaseous emissions of bio-jet fuel blends in a gas turbine combustor are described in [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%